NEW APPROACHES TO PREVENTION AND TREATMENT OF EARLY AND LATE POSTOPERATIVE LIMPHORRHEA - O. E. Fatuev; N. S. Kozlov; G. M. Korolyuk; I. A. Ratke; A. V. Ronzin; N. S. Stepanyants; E. N. Belov; V. V. Safronova; I. M. Vagabova (Исследования и практика в медицине, 2019)
Purpose of the study. To provide prevention of early and treatment of late postoperative lymphorrhea in patients with oncological profile using fluorescent lymphography, photodynamic, radiation and endolymphatic lymphostatic therapy.Patients and methods. In the process, the results of treatment of 2 groups of patients were evaluated. Group I (main group) — 310 people — were patients with localized malignant tumors, who underwent elective surgical treatment and to whom were applied developed measures for the prevention of early and treatment of late postoperative lymphorrhea using fluorescent lymphography (168 people), photodynamic (68 people), radiation (48 people) and endolymphatic lymphostatic therapy (26 people). Group II (control group) — 310 people — who underwent elective surgical treatment of tumor diseases of similar localization using standard measures for the treatment of postoperative lymphorrhea (punctures, pressure dressings, etc.). The groups were comparable by sex, age, nosology and the volume of surgical interventions.Results. We estimated the volume and duration of lymphorrhea by the amount of allocated to the drainage and evacuated puncture lymph. In the control group, the average lympho-loss in the hospital was 59.6 ml, at the outpatient stage — 15.8 ml. Of the 310 patients in the control group, postoperative complications were identified in 29 (9.4%) patients: wound suppuration (11), abscesses (4), pleural empyema (2), thromboembolism (3), adhesive disease (6), pyelonephritis (2) and myocardial infarction (1). Initial lymphorrhea, more than 100 ml per day, was present in 27 (93%) of these patients.Lymphorrhea in the main group in the hospital was 32.7 ml, and at the outpatient stage — 8.1 ml. Complications in the main group were detected in 13 (4.2%) patients: wound suppuration, anastomotic failure and fistula — 3, abscesses — 1, thromboembolism — 1, bleeding from duodenal ulcer — 1, adhesive disease — 7.After the application of the proposed measures for the prevention and treatment of lymphorrhea in the main group, the duration and volume of lymphorrhea decreased almost twice, as did the frequency of postoperative complications.Conclusion. Prolonged lymphorrhea leads to an increase in the incidence of postoperative complications. Fluorescent lymphography, photodynamic therapy, radiation therapy and endolymphatic lymphostatic therapy, taking into account indications and contraindications to each of these methods, can be used for the diagnosis, prevention and treatment of postoperative lymphatic lesions. An individual approach to the prevention of postoperative lymphorrhea leads to a decrease in its volume and duration, a decrease in the frequency of postoperative complications, a reduction in the patient’s stay in hospital and at the outpatient stage and allows for the timely start of special treatment in cancer patients.